Concept of struggle in the lyric poetry of Lesia Ukrainka (Literatures of the World: Poetics, Mentality and Spirituality, 2013)
The creative realization's features of the concept of struggle in Lesya Ukrain-ka's lyrics are discussed in the article. The author reveals the specific presentation of the consept of the struggle in the poetry collections by Lesia Ukrainka. The different faces of the creative interpretation according to the consept are highlighted in the poetess’ lyrical works.
Keywords: concept; struggle; lyrics; neoromanticism